Using thermostabilizers in industrial refrigeration units with circulating water supply system - V. A. Maksimenko; V. A. Chernyshev; A. Zh. Shirazhiyev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this article modernization of industrial refrigeration unit with circulating water supply system by applying a thermostabilizer for additional water cooling is under discussion. A technical scheme is developed, calculations needed for equipment selection and its payback period are made